Happy in our skin - Manushkin, Fran (Candlewick Press, 2015)
Bouquets of babies sweet to hold: cocoa-brown, cinnamon, and honey gold. Ginger-coloured babies, peaches and cream, too - splendid skin for me, splendid skin for you! A delightfully rhythmical read-aloud text is paired with bright, bustling art from the award-winning Lauren Tobia, illustrator of Anna Hibiscus, in this joyful exploration of the new skin of babyhood. A wonderful gift book for new mums and toddlers, all children can see themselves, and open their eyes to the world around them, in this sweet, scrumptious celebration of skin in all its many, many, wonderful forms.